Education Cities. Issue 2 (April 2014) - Shaked, Haim
In recent years, several cities in Israel have labeled themselves Education Cities, concentrating on education as their central theme. Employing qualitative techniques, this article aims to describe, define, and conceptualize this phenomenon as it is being realized in three such cities. Findings show that Education Cities differ from one another but have common principles. Four main characteristics of Education Cities are presented: an arranging concept, a unique educational style practiced in the local school system, local government's involvement in education, and collaborations among various city entities. Further research should examine Education Cities' outcomes and follow further developments of this concept.